Using keywords to construct wuzzle-picture-puzzles for the purpose of mastering management and organisational behaviour terminology. Issue 6 (2nd June 2016) - Dunphy, Steve
ABSTRACT: A pedagogical exercise for the purpose of mastering terms associated with management and organisational behaviour terminology was tested in four sections of an undergraduate, Introduction to Business Administration and Organizational Behaviour course at a regional university. The example required students to draw from terminology across the liberal arts and sciences curriculum. Four sections of the class were examined. Two sections were exposed to a treatment effect and were designated as 'experimental groups'. Two sections were not exposed to this treatment effect and were designated as 'control groups'. It was hypothesised that the students in the experimental sections who were exposed to the wuzzle-picture-puzzle treatment effect would outscore the students in the control sections who were not. A one-way t -test showed that the experimental groups significantly outscored the control groups. Limitations are noted and suggestions for future research are given.